Thermomechanical analysis of an elastoplastic rough body in sliding contact with flat surface and the effect of adjacent contact asperity - Jianmeng Huang; Chenghui Gao; Jingjing Chen; Xiezhao Lin; Zhiying Ren (Advances in Mechanical Engineering, 2015)
The study of the instantaneous frictional temperature, stress, and equivalent plastic strain generated when two surfaces are in frictional sliding process plays a significant role in understanding friction and wear mechanism. A thermomechanical coupling model between a rough body and a flat body is established. The model integrates the heat flux coupling between the sliding surfaces and considers the effects of the interaction among contact asperities and elastoplastic deformation of the rough body. The thermomechanical problem under this three-dimensional model is solved by the nonlinear finite element methods in ABAQUS software. The results show that the temperature, contact pressure, and stress are coupled. The results of the real contact area and the instantaneous frictional temperature, contact pressure, and VonMises equivalent stress on the local contact region fluctuate obviously due to the interaction among the adjacent contact asperities. The influence of asperity interaction is not constant but intermittent. Its time interval is related to the added interaction of a new adjacent contact asperity. The fluctuation of the VonMises equivalent stress makes the equivalent plastic strain of the frictional surface layer accumulate continually which might cause fatigue wear and plastic deformation wear of the material when the frictional rotating process was repeated.